Mot en hållbar utveckling för meningsfull användning av flera språk nationellt? Ungas uppfattningar om en- och flerspråkighet vid kommunikation i Finland och Sverige - Heittola, Sanna; Björklund, Siv (VAKKI ry, 2023)
In this article, we study how language majority and minority youth (Finnish-, Swedish- and Sami-speaking youth) in Finland and Sweden perceive the possibility to use languages in their countries. Our theoretical underpinnings are inspired by language policy and language ecology with a special focus on possible impacts of national language policy on language ideologies and language praxis circulating in increasingly multilingual societies. The results show that several statistically significant differences can be revealed between the youth from different countries and with different first languages. The differences indicate that national policy seems to have an effect on language ideologies among the participants. Nevertheless, the youth shares a common belief of the importance of multilingualism even if they recognize the practical challenges that people who cannot use the majority language of the country can face. Language is perceived not only as a medium for communication but also as an important part of the individual’s identity and culture. The result of this study shows that the youth perceives the use of different languages in their country of residence as self-evident.